JOCOWI SOLO STRATEGI JITU PENYELESAIAN MASALAH PKL LIAR DI KOTA SEMARANG - Susilowati, Desi Tri; Utami, Tri; Inaiyah, A’imatul; H., Hartiningtyas (Program Kreativitas Mahasiswa - Gagasan Tertulis, 2013)
Arrangement of vendor on the sidewalk in Semarang to note, because if it is not addressed it will interfere with the citys layout. But good communication approaches such as social groups, and cultural approaches humanisik integrated approach in communication strategy well by the city government. Because otherwise it would result in a clash between street vendors party wild with the city government. Communication strategy JOCOWI SOLO (Join Communication with Balancing Solution) into an integrated program approach and the continuous process of communication that emphasizes the balanced between the parties concerned so as to become an adaptive solution to accommodate a variety of issues related to illegal street vendors.